Efetividade do flúor e da escovação e eficácia dos materiais de colagem ionômero de vidro e resina composta na reversão das microporosidades criadas pelo condicionamento ácido no esmalte dentário - Praxedes Neto, Otávio José (2008)
The objectives of this clinical study was to evaluate the use of the toothpaste with fluoride and without fluoride and the daily tooth brushing are effective in the reversion of the dental enamel conditioned by acid. Another objective of this clinical study was to evaluate if the positioning of orthodontic accessories with glass ionomer cement helps in the reversion of the dental enamel conditioned by acid, when compared to composed resin. One hundred and twenty teeth were selected with indication of extraction by orthodontic reasons. The 30 volunteers were divided, randomly, in two groups. A group used toothpaste without fluoride and the other with it. The teeth of the sample were shuffled, in each volunteer. The teeth were conditioned by the 37% orthophosphoric acid. One of the conditioned teeth stayed in the mouth and suffered action of the abrasion for the tooth brushing, in another teeth a stainless steel mesh protection was positioned with glass ionomer cement, in another tooth the screen was glued with composed resin, in a fourth tooth (the control) was only conditioned after the extractions, 60 days later. All the teeth were appraised through DIAGNOdent, MEVA and EDS. In the obtained data it was possible to observe that there were not statistic significant differences in any comparison, even in the group that did not have access to the fluoride in the toothpaste as in the other that had. According with the used methodology, it was possible to observe too that there was not statistic significant differences in any comparison, even in the group that had the stainless steel mesh positioned with glass ionomer cement as in the group that the stainless steel mesh was positioned with composed resin. However, it was observed that there was an improvement in the topography of the enamel in all the teeth. The accomplishment of this study was facilitated due to the participation of the researchers' of the health area (dentistry), materials engineer, physics and chemistry. The researchers were originating from the Federal University of Rio Grande do Norte and of the University of Queensland, in Australia. This interdisciplinary group was decisive in the accomplishment of the study. It can be concluded that the enamel tends to return to its initial aspect, even if the patient does not have access to fluoride. That is probably due the action of the abrasion for the tooth brushing and mastication. In spite of it not being significant, it is suggested that the conditioned enamel was more resistant to the abrasion in the group that had access to fluoride. It was also possible to conclude that the fluoride liberated by the glass ionomer was not enough to provide a significant difference in the enamel conditioned by the acid, when compared with the composed resin, even in the group that did not use fluoride in the toothpaste as in the group that used